Investigating attitudes of nurses working in a state hospital towards prevention of pressure ulcers - Aziz Bulut; Çiğdem Aksu; Aliye Bulut; Mehtap Aslan (Genel Tıp Dergisi)
Objective: This study was conducted in order to investigate the attitudes of nurses working in a state hospital towards prevention of pressure ulcers. Material and Methods: The population of the present study consisted of a total of 246 nurses, who were working in a public hospital located in a city center in Eastern Anatolia Region. The study, it was attempted to reach the whole population, and the data were collected from 241 nurses who voluntarily participated in the study. A “Questionnaire” with 31 questions, which was prepared by the researchers, was used to collect the data. The data on the questionnaire prepared by the support of literature were collected using Nurse Information Form with 18 questions to investigate attitudes of nurses towards prevention of pressure ulcers as well as Attitude Towards Pressure Ulcer Prevention Instrument consisting of 13 questions. Results: The nurses with high school degree were determined to have higher attitudes towards the effect of pressure ulcers, towards the personal responsibility to prevent pressure ulcers, and towards the effectiveness of prevention of pressure ulcer. Attitudes of the nurses with high school degree towards personal sufficiency to prevent pressure ulcers were higher and the difference between the groups was significant (p<0.05). Conclusion: The present study revealed that attitude levels of nurses towards pressure ulcer prevention had some deficiencies. Within this context, each institution should determine pressure ulcer care protocols appropriate to standards and innovations, develop clinical practice guides, and ensure supervision of their convenience.